10-Year-Old Female with Acute Abdominal Pain with Pancreatic Mass. (9th October 2017) - Powers, Charles K.; Posa, Molly; Rajderkar, Dhanashree; Otero, Jaclyn
Abstract : A previously healthy 10-year-old female presented to a local emergency department following three days of nausea and vomiting diagnosed with a solid pseudopapillary tumor. Solid pseudopapillary neoplasms are a rare form of pancreatic cystic neoplasm that typically presents in young females in their 20–30s and are very rare in children. These neoplasms often present as an asymptomatic tumor found on incidental imaging. When symptomatic they most commonly present with abdominal pain and can also cause a palpable abdominal mass, weight loss, gastrointestinal obstruction, and nausea and vomiting. Timely diagnosis of this rare neoplasm is very important because complete resection of the tumor is the definitive treatment and leads to an excellent long-term survival.